Islamic knowledge portal: An analysis on knowledge portal requirements - Che Cob Z.; Ali N.; Sulaiman H.; Wan Mazuri W.M.I. (Asian Research Publishing Network, 2023)
In this paper, drawing upon the literature review and empirical data, we address the importance of knowledge sharing from Islamic perspective and the relevancy of Knowledge Management (KM) for sharing knowledge of Islam. We propose Islamic Knowledge Portal as a tool to effectively manage the knowledge of Islam to be a righteous and successful Muslim. In addition, this paper reviews successful implementation of KM portal in several organizations and identifies the important functional specifications to build such system. A survey results are used to empirically investigate the knowledge requirements for Islamic Knowledge Portal, and the findings from these activities are used to identify the required knowledge content and to design the important features for Islamic Knowledge Portal. 2006-2015 Asian Research Publishing Network (ARPN).